Informed Consent, Use, and Storage of Digital Photography Among Mohs Surgeons in the United States. Issue 3 (March 2016) - Rimoin, Lauren; Haberle, Sasha; DeLong Aspey, Laura; Grant-Kels, Jane M.; Stoff, Benjamin
Abstract : BACKGROUND: Digital photography is pervasive in dermatology. Potential uses include monitoring untreated disease, disease progression and treatment response, evaluating medical and cosmetic treatment, determining surgical sites, educating trainees and colleagues, and publishing reports in scientific journals. However, the nature of use, storage, and informed consent practices for digital photography among dermatologic surgeons has not been investigated. OBJECTIVE: This study used a comprehensive survey to elucidate these elements to better define standard practice. MATERIALS AND METHODS: A survey was created on SurveyMonkey. An email with the survey link was sent to all members of the American College of Mohs Surgery listserv with 2 follow-up emails. RESULTS: One hundred fifty-eight Mohs surgeons responded to the survey. Respondents indicated a wide variety in the type of camera and storage modality used for patient photographs. There was a variety of opinions on how to conceal a patient's identity when using photographs for educational purposes, and what features of a photo make it identifiable. CONCLUSION: Dermatologic surgeons vary widely on practices of photo storage and opinions of identifiability. Dermatology as a specialty may consider generating a consensus statement on appropriate use and storage of digital photography in dermatology practice.